2017
DOI: 10.1007/978-3-319-57193-5_15
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury as a Trigger of Neurodegeneration

Abstract: Although millions of individuals suffer a traumatic brain injury (TBI) worldwide each year, it is only recently that TBI has been recognized as a major public health problem. Beyond the acute clinical manifestations, there is growing recognition that a single severe TBI (sTBI) or repeated mild TBIs (rTBI) can also induce insidious neurodegenerative processes, which may be associated with early dementia, in particular chronic traumatic encephalopathy (CTE). Identified at autopsy examination in individuals with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 138 publications
1
49
0
Order By: Relevance
“…In the present study, we have revealed that widespread degenerating neurons are increased in the cortex, striatum, and hippocampal CA1 in both hemispheres long-term 24 weeks after a severe CCI-TBI. It has been shown that the widespread neurodegeneration after TBI is tightly linked to cognitive impairments [13,40]. The present study has demonstrated that SCF+G-CSF ameliorates long-term neurodegeneration in the contralateral frontal cortex and hippocampus remote from the injury site.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study, we have revealed that widespread degenerating neurons are increased in the cortex, striatum, and hippocampal CA1 in both hemispheres long-term 24 weeks after a severe CCI-TBI. It has been shown that the widespread neurodegeneration after TBI is tightly linked to cognitive impairments [13,40]. The present study has demonstrated that SCF+G-CSF ameliorates long-term neurodegeneration in the contralateral frontal cortex and hippocampus remote from the injury site.…”
Section: Discussionsupporting
confidence: 66%
“…155 (c) Rat-Aβ(1-16) dimer (Zn 2+ ); pdb 2li9. The rat Aβ (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) peptide also binds Zn 2+ and other metal ions, despite lacking the His13 residue of human Aβ chemical shifts), while in mature fibrils, these residues extend the N-terminal β-strand segment.…”
Section: Metal Ionsmentioning
confidence: 99%
“…DAI, as a type of TBI, is associated with cytoskeletal alterations, represented by swellings or varicosities along the axons and terminal bulbs [ 34 , 35 , 36 ]. These axonal alterations may be caused by mechanical disruption, and subsequent increasing intracellular Ca 2+ influx by the breaches in the axolemma [ 37 , 38 , 39 ].…”
Section: Tbi and Oxidative Stressmentioning
confidence: 99%